Volume 4: Offshore Geotechnics; Ronald W. Yeung Honoring Symposium on Offshore and Ship Hydrodynamics 2012
DOI: 10.1115/omae2012-83707
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Underwater Piling Noise Mitigation System: Using Hydro Sound Dampers (HSD)

Abstract: The aim of the recently published climate control by the German Federal Ministry for the Environment, Nature Conservation and Nuclear Safety (BMU) is a reduction of the German greenhouse gas emissions down to 20 % in 2050, compared to the generated greenhouse gas in 1990. To reach the given target a huge growth in renewable energy is necessary. One of the most potential possibilities to produce renewable energy in Germany will be the installation of offshore wind turbines. During the installatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, in practice, achieving a uniform distribution of free air bubbles in water is challenging due to varying ambient hydrodynamic conditions. Larger air bubbles with lower resonate frequency are more efficient at attenuating lower-frequency sounds (<1 KHz), but are relatively unstable and challenging to produce (Kuhn et al 2012). Therefore, air bubble curtains are typically more efficient at attenuating higher frequency sounds (400-6,400 Hz; Wursig et al 2000).…”
Section: Acoustic Dampingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in practice, achieving a uniform distribution of free air bubbles in water is challenging due to varying ambient hydrodynamic conditions. Larger air bubbles with lower resonate frequency are more efficient at attenuating lower-frequency sounds (<1 KHz), but are relatively unstable and challenging to produce (Kuhn et al 2012). Therefore, air bubble curtains are typically more efficient at attenuating higher frequency sounds (400-6,400 Hz; Wursig et al 2000).…”
Section: Acoustic Dampingmentioning
confidence: 99%
“…Wursig et al (2000) observed a 3-5 dB sound reduction in overall broadband frequencies, and up to 20 dB in the 1.6-6.4 kHz bands. In general, technical limitations of effectively implementing bubble curtains include achieving effective distribution around the sound source, maintaining a consistent distribution of bubble sizes, and the lack of sound mitigation at lower-range frequencies (<1 kHz) (Nehls et al 2007;Kuhn et al 2012).…”
Section: Acoustic Dampingmentioning
confidence: 99%
See 1 more Smart Citation